Needs and Enabling Factors Influencing Elderly Workforce Participation in Cattle-Raising Community Enterprises: A Qualitative Study in Tak Province - Mofu, Natchiya (Journal of Public Administration Chiang Rai Rajabhat University, 2025)
Thailand is rapidly transitioning into an aging society, leading to labor challenges, especially in the agricultural sector that still relies heavily on elderly workers. This qualitative study aimed to examine the needs of elderly laborers in participating in production processes, analyze cultural and social capital factors influencing participation, and synthesize supportive models suitable for grassroots economic systems. Data were collected through structured interviews and focus group discussions with 24 key informants, including elderly laborers, community leaders, and their family members in Mueang District, Tak Province. The instruments were validated for content accuracy. The findings revealed that elderly workers expressed high demand for roles that utilize their experience, such as cattle care and knowledge transfer, though limitations due to health and work environment were noted. Furthermore, four forms of cultural capital-physical, financial, intellectual, and human—played significant roles in motivating elderly participation and fostering a sense of self-worth. The results suggest a policy-relevant approach to strengthening elderly labor engagement in community enterprises sustainably.